Fagin’s Criminal Thought in Charles Dickens’ Oliver Twist - Rahmi Munfangati; Desi Ramadhani (Institut Agama Islam Negeri Palopo, 2020)
This research aims to reveal Fagin’s criminal thought in Charles Dickens’ Oliver Twist and to examine the factors that influence Fagin’s criminal thought presented in the novel. This research is classified into library research. The subject of the research is Oliver Twist, Charles Dickens’ fiction novel. The novel is used as the primary source, while books, journals, and articles related to criminal thought theories in psychology were taken as the secondary source. A psychological approach is applied to analyze the data. The collected data were analyzed qualitatively. In analyzing the data, the researcher took five steps. The data were collected from reading and re-reading the text, identifying those that embody criminal thinking, categorizing them based on the objectives of the research, comparing them to the theoretical frameworks, and finally interpreting them using a psychological approach. After conducting the research, it can be drawn some conclusions; first, by seeing the eight aspects of criminal thought, Fagin has five aspects which are classified in the high category, and second, the factors that influence Fagin’s criminal thought reflected in the novel are societal and economic, neighbor-hood and local institutions, and drugs.